PHYSIOTHERAPY MANAGEMENT OF BREATHING EXERCISE AND MOBILIZATION OF THE THORAX CAGE IN CASES OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD): A CASE STUDY - Mufidayanti, Arum; Supriyadi, Arin (Universitas Muhammadiyah Surakarta, 2021)
Introduction : Chronic Obstructive Pulmonary Disease (COPD) is a disease with persistent respiratory symptoms and chronic airflow limitation due to significant exposure to noxious particles or gases combined with a variety of host factors including genetics, airway hyperresponsiveness, and poor lung growth during childhood. The purpose of this study was to determine the effectiveness of breathing exercise combined with mobilization of the thorax cage on increasing activity tolerance. Case Presentation : A 65-year-old man with history of COPD presented with severe shorthness of breath, chest pain and cough with difficulty in expelling phlegm. The patient had smoking history and hypertention. The spirometry examination result showed the FEV1 prediction was 50%. Management and Outcome : The treatment used in this study were breathing exercise combined with mobilization of the thorax cage. The evaluation result showed from day 1 to day 4 there were BORG scale from 5 to 2, CAT scale from 33 to 11, mMRC scale from 4 to 2 and there was significant improvement from thorax expansion. Discussion : Breathing exercise combined with mobilization of the thorax cage decreased the sensation of dyspnea patient with COPD and improved the thorax expansion by loosened the airway and increased the upper-limb joint range of motion. Conclusion: Breathing exercise combined with mobilization of the thorax cage has positive impact on improved exercise/activity tolerance patient with COPD.